Effect of epiphyseal plate fenestration on bone growth in dogs - Sh., SALMAN R.; A., SALH S.; H., TOWJ ,J, (The Iraqi Journal of Veterinary Medicine, 2021)
This study is designed to know the effect of fenestration on the epiphyseal plate as amethod to truma and know it is effect on length of long bones Eleven of local breed bitched is used in this research are put in four group depending on the site of operation , tthree dogs in each group except for the last group which included tow dogs as follows: *the first group : the operation was performed on the distal epiphyseal plate of the femur *the second group : the operation was performed on the proximal epiphyseal plate of the tibia and fibula *the thrid group : the operation was performed on the distal epiphyseal plate of the tibia and fibula *the fourth group : the operation was performed on all sites mentioned above the cases was folowed up clinically and radiographically for six months , an x-Ray film was taken every fifteen days for the first three months and monthly for the other three months, the other hind limb of the animal was used for comparison. the clinical and radiographical follow up showed that fenestration of the epiphyseal platewas succssful to induce epiphysiodesis in first, third and fourth group without complication while it failed in the second group.